Greetings from Tobago, B.W.I. - (:unkn) unknown (H.O. Thomas, [Trinidad and Tobago], 2011)
Description printed on the back of the postcard: "Blue sea and clean white sand visible through the coconut trees at Arnos Vale, Plymouth - Tobago." This postcard is addressed to Mr. and Mrs. George F. Pierrot, Michigan, United States of America. Postcard number 22517.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Beaches--Trinidad and Tobago; 1958; Palms--Trinidad and Tobago; Scenic overlooks--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Plymouth